Nuclear Resonance Fluorescence off 54Cr: The Onset of the Pygmy Dipole Resonance. (June 2016) - Ries, P C; Beck, T; Beller, J; Krishichayan,; Gayer, U; Isaak, J; Löher, B; Mertes, L; Pai, H; Pietralla, N; Romig, C; Savran, D; et al.
Abstract: Low-lying electric and magnetic dipole excitations (E1 and M1) below the neutron separation threshold, particularly the Pygmy Dipole Resonance (PDR), have drawn considerable attention in the last years. So far, mostly moderately heavy nuclei in the mass regions around A = 90 and A = 140 were examined with respect to the PDR. In the present work, the systematics of the PDR have been extended by measuring excitation strengths and parity quantum numbers of J = 1 states in lighter nuclei near A = 50 in order to gather information on the onset of the PDR. The nuclei 50, 52, 54 Cr and 48, 50 Ti were examined via bremsstrahlung produced at the DArmstadt Superconducting electron Linear Accelerator (S-DALINAC) with photon energies up to 9.7 MeV with the method of nuclear resonance fluorescence. Numerous excited states were observed, many of which for the first time. The parity quantum numbers of these states have been determined at the High Intensity Gamma-ray Source (HIγS) of the Triangle Universities Nuclear Laboratory in Durham, NC, USA. Informations to the methods and the experimental setups will be provided and the results on 54 Cr achieved will be discussed with respect to the onset of the PDR.